Biogas production from renewable lignocellulosic biomass - Gnanambal, Venkatachalam Sundaresan; Swaminathan, Krishnaswamy (International Journal of Environment, 2015)
Effect of raw and biologically treated lignocellulosic biomass using cow dung slurry for biogas production is reported. Biomass is an energy source. Water containing biomass such as sewage sludge, cow dung slurry and lignocellulosic waste, has several important advantages and one of the key feature is renewability. Cow dung slurry has the potential to produce large amounts of biogas. Four categories of bacteria viz., hydrolytic, fermentative, fermentative acidogenic and acidogenic-methanogenic bacteria are involved in the production of biogas. The different characteristics of the cow dung slurry were determined according to standard methods. Hemicellulose, cellulose and lignin content of the lignocellulosic waste were also determined in our earlier studies. The substrates were digested under anaerobic condition for 5 days. The total biogas and methane produced during anaerobic digestion were estimated on 5th day. The total biogas produced during digestion was estimated by water displacement method. Biological methane production was estimated by using Saccharometer. DOI: http://dx.doi.org/10.3126/ije.v4i2.12662 International Journal of Environment Vol.4(2) 2015: 341-347